MiR-125a-3p and its Targets: Promising Biomarkers for Ovarian, Liver, and Breast Cancers, Offering a Beacon of Hope for More Effective Diagnosis and Treatment Strategies - Anwer, Eman Kamaleldien (AUC Knowledge Fountain, 2025)
Cancer is a worldwide health problem with various genetic and epigenetic alterations, resulting in disease heterogeneity. Effective diagnostic, therapeutic, and monitoring markers have been determined recently; however, new diagnostic, prognostic, and therapeutic markers are needed. MicroRNAs (miRNA), short non-coding RNAs, have a highlighted role in cancer progression, migration, and programmed cell death. Our study aims to investigate the significance of miR-125a-3p and its downstream targets in breast (BRCA), hepatocellular (HCC), and ovarian (OVCA) malignancies and their possibility as diagnostic biomarkers and targets for therapeutic agents. Bioinformatics and online tools were used to determine the miRNA-predicted downstream targets, analyze GEO datasets, and perform functional annotation of the miRNA-target genes. We tested the levels of miR-125a-3p and its targeted genes expression in SKOV-3, Hep G2, and MCF-7 cell lines in addition to ovarian cancer tissue samples and SKOV-3 treated with paclitaxel (PTX) using qPCR. Combining the in silico and in vitro analyses, miR-125a-3p was significantly downregulated in BRCA, OVCA and HCC. At the same time, it was significantly elevated in the ovarian cancer tissue samples obtained from pre-treated patients, indicating that miR-125a-3p is an oncosuppressor miRNA. Our in silico analysis determined BOK and ARHGEF39 as potential downstream targets of miR-125a-3p. BOK was significantly downregulated in BRCA and HCC cancers; on the contrary, its expression was raised in OVCA. It was also upregulated in OVCA pre-treated samples and cell lines. ARHGEF39 was significantly upregulated in BRCA, HCC, and OVCA and downregulated in pre-treated OVCA samples and cell lines. Finally, our findings suggest miR-125a-3p, BOK, and ARHGEF39 could serve as possible diagnostic and monitoring biomarkers as well as therapeutic targets for cancer treatment.